New IMB16-4 Hot-Melt Extrusion Preparation Improved Oral Bioavailability and Enhanced Anti-Cholestatic Effect on Rats - Li Y; Tian C; Song X; Du M; Zhang G; Liu H (Dove Medical Press, 2023)
Yuqin Li,1,2 Changlin Tian,1,2 Xiaofei Song,3 Mengying Du,4 Guoning Zhang,5 Hongtao Liu2 1Graduate School, Hebei Medical University, Shijiazhuang, People's Republic of China; 2Hebei Key Laboratory of Metabolic Diseases, Hebei General Hospital, Shijiazhuang, People's Republic of China; 3Department of Otolaryngology, Hebei General Hospital, Shijiazhuang, People's Republic of China; 4Performance Assessment Department, Quality Management Department, Hebei General Hospital, Shijiazhuang, People's Republic of China; 5Institute of Medicinal Biotechnology, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Hongtao Liu, Email lhtyl16@126.comBackground: Cholestasis is challenging to treat due to lacked effective drugs. N-(3,4,5-trichlorophenyl)-2 (3-nitrobenzenesulfonamido) benzamide, abbreviated as IMB16-4, which may be effective for the treatment of cholestasis. However, its poor solubility and bioavailability seriously obstruct the research programs.Methods: A hot-melt extrusion (HME) preparation was first applied to increase the bioavailability of IMB16-4, the oral bioavailability, anti-cholestatic effect and vitro cytotoxicity of IMB16-4 and IMB16-4-HME were evaluated. Meanwhile, the molecular docking and qRT-PCR were used to validate the mechanism behind.Results: The oral bioavailability of IMB16-4-HME improved 65-fold compared with that of pure IMB16-4. Pharmacodynamics results demonstrated that IMB16-4-HME prominently decreased the serum levels of total bile acid (TBA) and alkaline phosphatase (ALP), but elevated the level of total bilirubin (TBIL) and direct bilirubin (DBIL). Histopathology revealed that IMB16-4-HME at lower dose exhibited stronger anti-cholestatic effect compared with pure IMB16-4. In addition, molecular docking demonstrated that IMB16-4 has great affinity with PPARα, and qRT-PCR results revealed that IMB16-4-HME significantly elevated the mRNA expression level of PPARα, but decreased the mRNA level of CYP7A1. Cytotoxicity assays demonstrated that the hepatotoxicity of IMB16-4-HME was absolutely attributed to IMB16-4, and the excipients of IMB16-4-HME may increase the drug load within HepG2 cells.Conclusion: The HME preparation significantly increased the oral bioavailability and anti-cholestatic effect of pure IMB16-4, but caused liver injury at high dose, which require a dose balance between the curative effect and safety in the future research.Keywords: IMB16-4, IMB17-15, peroxisome proliferator activated receptor α, cholestasis, molecular docking